O bem estar vocal na formação de professores - Fantini, Leila de Abreu (2010)
Investigate the importance given to vocal health during teacher s graduation, by coordinators of Education courses of the state of São Paulo. Teachers are a professional at risk, many times, sent away from their work area due to voice disorders. This problem is universal, confirmed by studies. This situation can be overturned the moment teachers receive the necessary information, during his/her graduation. This study, of qualitative exploratory nature, was developed by semi-structured interviews recorded with coordinators of Education courses of the state of São Paulo. The following questions were asked: 1. What does vocal health mean to you?; 2. Are there actions in favor of vocal health in the institution you coordinate? Which actions?; 3. How do you see the function of the speech therapist in teachers vocal health? The participants signed the termo de consentimento livre e esclarecido. The data was written and the speeches classified by frequency of similitude and content, grouped into theme categories. The coordinators mentioned parts of the concept of vocal health. According to the participants, in most of the institutions, there aren t any continuous prevention programs designated to teacher s vocal health. The majority agrees in having a speech therapist in the university to assist the teachers, through orientation or speech therapy, when a disorder already exists. The insertion of vocal health in teacher s graduation curriculum was commented. The programmed content of the Education courses in which the coordinators work was brought up, and even though the coordinators highlight the importance of vocal health, the curriculums of the courses do not mention this subject. We propose the insertion of themes regarding workers health in these curriculums, including vocal health